Understanding the Lived Experience of Persons Who have a Different Sense of Hearing - Aquino-Russell, Catherine Elma (Curtin University, 2003)
Hearing loss is a silent, often overlooked condition which deprives people of the most basic of human needs--the ability to communicate effectively. The notion that there is a dearth of understanding by health care professionals when caring for persons with hearing loss has been acknowledged. This research study aimed to describe the meaning of what it is like to live with a different sense of hearing for seven Canadian participants. The process of inquiry was guided by Parses human becoming theory for nursing (1981, 1987, 1992, 1998). The Giorgi (1970, 1971, 1975, 1985, 1989, 1992) modification of the phenomenological method was used for analysis-synthesis. Five women and two men employed and ranging between 25 and 70 years shared their lived experiences with the researcher via email correspondence. Confidentiality and anonymity were assured. Participants were asked to write about what it is like for them to live with a different sense of hearing. The central finding of this study was: Living with a different sense of hearing is experiencing the joy-sorrow of hearing-not hearing unfolding through discovering gained-lost communication surfacing all-at-once with diminished-enhanced feelings of self while choosing the rhythm of revealing-concealing amid potential regard-disregard of others. The findings of this research build on Parses (1981, 1998) theory of human becoming and may enhance nurses understanding of what it is like to live with hearing loss, which may in turn alter the way nurses structure practice with persons who live with a different sense of hearing, making a difference in their quality of life.